Evaluation Performance Covid-19 Tasikmalaya Task Unit - Danial Kusumah; Dede Aji (Future Science, 2021)
The role of the Covid-19 Task Force determines the effectiveness of handling the pandemic in Tasikmalaya City. Performance evaluation is an instrument to measure the gap between the established policies and the resulting achievements. The analytical method in this study uses a literature study through a qualitative approach. By using the indicators of transparency, participation, responsiveness, and accountability, it was found that the Covid-19 Task Force has shown good performance in efforts to accelerate the handling of the corona virus in the City of Tasikmalaya. However, continuous performance improvement is needed to be able to significantly reduce the number of positive cases